2021
DOI: 10.1111/phn.12918
|View full text |Cite
|
Sign up to set email alerts
|

Behavior in the use of face masks in the context of COVID‐19

Abstract: Objectives Investigation of potential erroneous behavior in the general public's use of face masks during the COVID‐19 pandemic. Design We conducted a naturalistic observational study in the period from April to June 2020. Sample In two western Austrian provinces, a total of 2080 persons were observed in front of 24 grocery stores. Measurement The frequencies and types of erroneous behavior in the use of face masks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
11
1
1
Order By: Relevance
“…In our study, only 3% of those who wore face masks were judged to be wearing them incorrectly, i.e., not covering both mouth and nose. This is very low compared to other studies that have observed face mask use in the community, where the proportion of users with only partial coverage of mouth and nose have been reported to be several times higher [19][20][21]. We have no good explanation for this striking difference, but it does illustrate that face mask practices probably vary considerably across contexts.…”
Section: Discussioncontrasting
confidence: 89%
“…In our study, only 3% of those who wore face masks were judged to be wearing them incorrectly, i.e., not covering both mouth and nose. This is very low compared to other studies that have observed face mask use in the community, where the proportion of users with only partial coverage of mouth and nose have been reported to be several times higher [19][20][21]. We have no good explanation for this striking difference, but it does illustrate that face mask practices probably vary considerably across contexts.…”
Section: Discussioncontrasting
confidence: 89%
“…We included 48 [ 14 –, 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] studies containing an observation component during the COVID-19 pandemic. In total these included at least 116,169 participants and at least 36,060,422 behavioural observational events.…”
Section: Resultsmentioning
confidence: 99%
“…Paradoxically, lack of awareness on the use of face masks has led many people in some nations to not always wear them, which has resulted in large numbers of human losses (Kellerer et al, 2021).…”
Section: A Lesson Learnedmentioning
confidence: 99%